1981
DOI: 10.1002/cber.19811140806
|View full text |Cite
|
Sign up to set email alerts
|

Beiträge zur Chemie des Bors, 118. Struktur und Dynamik von Hexamethylborazin‐Aluminiumbromid

Abstract: Aluminiumbromid koordiniert in seinem 1 : 1-Addukt mit Hexamethylborazin iiber ein N-Atom. Der Borazin-Ring verliert dadurch seine Planaritlt, seine BN-AbstBnde variieren zwischen 139 und 154 pm, wie aus der Rdntgenstrukturanalyse des monoklin kristallisierenden Addukts hervorgeht (R, = 0.076). Die Ringkonformation wird durch schwache intramolekulare und intermolekulare Br-B-Wechselwirkungen geprlgt. In Ldsung zeigt das Addukt fluktuierendes Verhalten oberhalb von 276 K. Contributions to the Chemistry of Boron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“… a Complexes have been experimentally observed in the solid state and in benzene/toluene solution. See refs and for details. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a Complexes have been experimentally observed in the solid state and in benzene/toluene solution. See refs and for details. …”
Section: Resultsmentioning
confidence: 99%
“…To date, only two examples of neutral borazine complexes featuring donor−acceptor (DA) σ-bonds are experimentally known. These are complexes of hexamethylborazine with acceptor molecules AlBr 3 and GaCl 3 , both compounds were synthesized and structurally characterized by the Nöth group in the 1980s. , More recently, Pinkas and co-workers demonstrated that the heavier group 13 analogue of borazine, the substituted alumazene [R 3 Al 3 N 3 R′ 3 ] (R = Me, R′ = (2,6- i Pr 2 C 6 H 3 )), forms a series of σ-complexes with donor molecules such as pyridines and nitriles . Very recently, Fan et al used donor properties of an amino group in 1,3,4,5,6-pentamethyl-2-aminoborazine to generate borazine-substituted Al 2 N 2 rings and borazine-based polymers .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the direct syntheses of Mn–arene complexes typically proceed in neat arene at reflux with Mn(CO) 5 Br in the presence of Ag(I) or AlCl 3 or, alternatively, using acidic conditions from Mn 2 (CO) 10 in the presence of HOAc F and (CF 3 CO) 2 O . Borazines react with most acids, including HOAc F and AlCl 3 , , and in our hands, reactions of Mn(CO) 5 Br with assorted Ag(I) salts in the presence of Me 6 B 3 N 3 did not afford the desired product. The poor reactivity is likely due to borazine’s weaker binding affinity in comparison to that of arenes, which decreases the associated driving force for the necessary ligand exchange reaction, due to competitive binding with many solvents and counteranions.…”
mentioning
confidence: 77%
“…In 2011, Liu and co-workers used a longer, but ultimately higher-yielding, sequence to prepare 1,2-BN-cyclo-hexane-based borazine 150. N,N-Bis(trimethylsilyl)but-3en-1-amine (152) in THF was treated with borane-THF complex to obtain the cyclic aminoborane intermediate 153 (Scheme 76). 125 Unpurified 153 was next reacted with KH to afford cyclic amidoborane 154.…”
Section: Scheme 74 Synthesis Of Borazatruxenes 123mentioning
confidence: 99%
“…N -Coordinated (1:1) complexes of B -trisubstituted borazines have been reported with AlCl 3 or AlBr 3 or GaCl 3 in toluene (Scheme 101 ). 152 153 154 The borazine ring in these complexes exist in a semi-chair conformation. Interestingly, addition of HBr to these complexes affords borazinium tetrabromoaluminates (R 3 B 3 N 3 H 4 ) + (AlBr 4 ) – .…”
Section: Borazine Metal Complexesmentioning
confidence: 99%